2008
DOI: 10.1016/j.jebo.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Informational cascades: A mirage?

Abstract: Nutzungsbedingungen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…For related studies, seeLux (1998); Goldbaum (2008) andOmurtag and Sirovich (2006).3 Recent studies includeCipriani and Guarino (2008) andSpiwoks et al (2008). The latter study provides experimental evidence on informational cascades.…”
mentioning
confidence: 99%
“…For related studies, seeLux (1998); Goldbaum (2008) andOmurtag and Sirovich (2006).3 Recent studies includeCipriani and Guarino (2008) andSpiwoks et al (2008). The latter study provides experimental evidence on informational cascades.…”
mentioning
confidence: 99%
“…In these instances, participants tended to move further away from Bayesian rationality than recognition of the identified errors warranted, suggesting failure by participants to fully recognize that rational choice can produce suboptimal outcomes. On the other hand, Huck & Oechssler (2000); Nöth & Weber (2003); Spiwoks et al (2008) found general failures of Bayesian rationality and overweighting of private signals, and therefore fewer cascades. That www.thebalticyearbook.org Evolution of Individualistic Norms 20 is, in these experiments people departed from individual rationality by taking their own private information too seriously-and thereby behaved in a way that, given some plausible informational structures, could increase expected market efficiency.…”
Section: Cooperation Coordination Imitation and Human Evolutionmentioning
confidence: 96%
“…Similarly, mixed results have been found in laboratory-based studies, in which both the decisions and the information on which they are based are observable (e.g., Cipriani & Guarino, 2005, 2009Spiwoks et al, 2008). The common finding from these studies is that participants do herd, but to a lesser extent than theoretical models predict.…”
Section: Herding In Financial Marketsmentioning
confidence: 99%
“…Empirical evidence for the phenomenon from financial markets is inconclusive (Lakonishok et al, 1992;Wermers, 1999;Sias, 2004). Similarly, mixed results have been found in laboratory-based studies, in which both the decisions and the information on which they are based are observable (e.g., Cipriani & Guarino, 2005, 2009Spiwoks et al, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 99%